2019
DOI: 10.1055/s-0039-1683874
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Functional and Structural Connectivity Are Associated with Cerebral Palsy at Two Years of Age

Abstract: Objective The accuracy of structural magnetic resonance imaging (MRI) to predict later cerebral palsy (CP) in newborns with perinatal brain injury is variable. Diffusion tensor imaging (DTI) and task-based functional MRI (fMRI) show promise as predictive tools. We hypothesized that infants who later developed CP would have reduced structural and functional connectivity as compared with those without CP. Study Design We performed DTI and fMRI using a passive motor task at 40 to 48 weeks' postmenstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Although the literature on fMRI in newborns with brain injury is still scarce, these findings are supported by a study performed on newborns with perinatal brain lesions, including NE due to presumed PA, which concluded that the CP group had reduced functional connectivity from the right supplementary motor areas when compared with the non-CP group [33]. However, they did not find any difference between the groups in brain activation during a motor task like the one used in our study.…”
Section: Discussionsupporting
confidence: 82%
“…Although the literature on fMRI in newborns with brain injury is still scarce, these findings are supported by a study performed on newborns with perinatal brain lesions, including NE due to presumed PA, which concluded that the CP group had reduced functional connectivity from the right supplementary motor areas when compared with the non-CP group [33]. However, they did not find any difference between the groups in brain activation during a motor task like the one used in our study.…”
Section: Discussionsupporting
confidence: 82%
“…Since our study was conducted on u-HCC, which is a different subject from the previous study, a new cutoff value needs to be established. CV ≥ 0.22, the median value for all patients, was applied in this study as a cutoff, as in previous studies [ 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that term-born children with PVL may have a more diffuse injury of white matter when compared to preterm children with PVL [14]. In both term and preterm infants, perinatal brain injury is the primary cause of cerebral palsy [19]. Structural MRI is the standard used to evaluate for brain injury in term and preterm infants with suspected brain injury apparent on ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…Structural MRI is the standard used to evaluate for brain injury in term and preterm infants with suspected brain injury apparent on ultrasound. It was found that Diffusion Tensor Imaging (DTI) and functional MRI obtained soon after birth are potential biomarkers to help predict CP in newborns with perinatal brain injury, thus facilitating early intervention to improve motor outcomes in infants at risk of CP [19]. Infants with perinatal brain injury and CP were shown to have reduced structural and functional connectivity within motor networks during the neonatal period when compared to infants with perinatal brain injury and normal motor outcomes [19].…”
Section: Discussionmentioning
confidence: 99%